Evaluating Students’ English Writing Project through Pear Deck - Lambok Hermanto Sihombing (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
riting is a fundamental language-learning skill, particularly in English. The writing of students could be assessed manually or electronically. Pear Deck is an interactive tool that helps students do their writing assignments digitally. It also helps teachers create an interesting writing class. In this study, the author aims to determine how Pear Deck could be utilized as an effective learning approach for assessing student writing. The author utilized a qualitative methodology and the instrument of this study was taken from 15 students’ writing at President University, Indonesia majoring in Communication. As another support, the dataset was collected from the official Pear Deck website, journal publications, and conference proceedings. The author applied the Language Assessment: Principles and Classroom Practices theory from H. Douglas Brown and the concept of Discourse Analysis in educational settings. This study revealed that Pear Deck is an effective option for assessing students' writing, particularly composing a paragraph in the English language. Asides from it, Pear Deck also has an interesting visual screen that makes the students curious to learn the following activities. This application is also equipped with an interactive feature that allows students to give written feedback to their friends.